Valuation of ecological resources : (CRC/Taylor & Francis, 2008)
Choosing the optimal management option requires environmental risk managers and decision makers to evaluate diverse, and not always congruent, needs and interests of multiple stakeholders. Understanding the trade-offs of different options as well as their legal, economic, scientific, and technological implications is critical to performing accurate assessments and making sound decisions.Valuation of Ecological Resources: Integration of Ecology and Socioeconomics in Environmental Decision Making examines various alternatives for determining the "value" of complex ecological resources. The book discusses how ecology, sociology, and economics influence environmental management decisions. The book further explores the scientific underpinnings of ecological valuation and the roles of regulatory and legislative bodies in the decision-making process. A series of case studies demonstrates the utility of various information sets, tools, and analytical frameworks.Summarizes the conclusions reached by the Ecological Risk Assessment Advisory Group during special workshops conducted by the Society of Environmental Toxicology and Chemistry (SETAC)Written by leading experts from industry, academia, and environmental regulatory agencies, this new text is an excellent resource for self-study as well as for courses in industrial ecology, environmental management, ecological risk assessment, environmental policy, and strategies for sustainability and corporate responsibility.